LANGUAGE LEARNING STRATEGY USED BY EFL LEARNERS IN INDONESIA - Nurhayati Ganinda; Rini Lindawati (Program Studi Pendidikan Bahasa dan Sastra Indonesia Universitas Islam Majapahit (UNIM) Mojokerto Indonesia, 2023)
This study aimed at finding the commonly used language learning strategy by EFL student in Indonesia. Literature review design is used in carrying the study. The source of the data is 25 scientific research about language learning strategy that used Strategy Inventory Language Learning (SILL) as the main instrument. The finding shows that metacognitive strategy is the most commonly used strategy by the learners, and it is followed by compensation strategy as the second most commonly used strategy. The least used strategy by the learners is Memory strategy.